lecture03 - Lecture 3 - Functions and Limits 3.1 Functions...

This preview shows pages 1–4. Sign up to view the full content.

Lecture 3 - Functions and Limits 3.1 Functions In the expression y = f ( x ) = x 2 + 3 we say that x is the independent variable and that y is the dependent variable . A function is a relationship between two variables such that to each value of the inde- pendent variable there corresponds exactly one value of the dependent variable. This is a rewording of what you may know as the so-called “vertical line test” for functions. The domain of a function is the set of all values of the independent variable for which the function is deﬁned. Examples: 1. Find the domain of f ( x ) = x 2 1 - x solution: In a question like this, we are trying to ﬁnd the largest possible domain. Here, the only potential problem is that the denominator could be 0. So the domain is every real number except 1. We write Domain = { x | x 6 = 1 } We will see later that the graph looks like this:

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
2. Find the domain of f ( x ) = 2 x - 3 solution: Here we need to make sure that what’s inside the square root is non-negative. So, 2 x - 3 0 x 3 2 So the domain is ± 3 2 , ) . Note that 3 2 is included. The graph looks like: Related to the domain is the range , which is the set of all y -values a function could possibly take. Composites If f and g are functions, then their composite, denoted f g , is deﬁned to be f ( g ( x )). In other words, apply g to x and then apply f to the result. Example: If f ( x ) = 1 + x 2 and g ( x ) = 2 x - 1, then f ( g ( x )) = f (2 x - 1) = 1 + (2 x - 1) 2 = 1 + (4 x 2 - 4 x + 1) = 4 x 2 - 4 x + 2 On the other hand, g ( f ( x )) = g (1 + x 2 ) = 2(1 + x 2 ) - 1 = 2 x 2 + 1
So f g 6 = g f , in general. Inverses Two functions f and g are inverses of each other if f ( g ( x )) = x and g ( f ( x ) = x . Normally, g is denoted f - 1 . So, f f - 1 ( x ) = x f - 1 f ( x ) = x Example: If f ( x

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 01/07/2010 for the course MAT mat1300 taught by Professor Pieterhofstra during the Fall '09 term at University of Ottawa.

Page1 / 9

lecture03 - Lecture 3 - Functions and Limits 3.1 Functions...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online